2022
DOI: 10.3390/gels8100631
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Weak Gel Structure of an Oil-Based Drilling Fluid by Using a Polyamide Wax

Abstract: Oil-based drilling fluids (OBDFs) are widely used, but there are common problems associated with them, such as low yield point and poor cutting–carrying and hole cleaning ability. In this paper, a polyamide wax (TQ-1) was synthesized from dimeric acid and 1,6-hexanediamine to improve the weak gel structure of OBDFs. The TQ-1 was characterized by Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Then the effect of the TQ-1 on the stability of the water-in-oil emulsion was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Weak gels are three-dimensional crosslinked systems consisting primarily of inter-and intramolecular crosslinkers, complemented by low concentrations of polymers and weak crosslinkers. As the concentration of crosslinkers increases, the network structure of the weak gel becomes more uniform and stronger (Huang et al [66]). The formation of weak gels with a spatial network structure by hydrogen bonding of polar amide groups in nonpolar solvents can make the emulsions exhibit excellent shear thinning and thixotropy, which substantially improves the gel strength and solves the problems of low yield point, rock carrying and poor borehole cleaning ability.…”
Section: In Drilling Fluidsmentioning
confidence: 99%
“…Weak gels are three-dimensional crosslinked systems consisting primarily of inter-and intramolecular crosslinkers, complemented by low concentrations of polymers and weak crosslinkers. As the concentration of crosslinkers increases, the network structure of the weak gel becomes more uniform and stronger (Huang et al [66]). The formation of weak gels with a spatial network structure by hydrogen bonding of polar amide groups in nonpolar solvents can make the emulsions exhibit excellent shear thinning and thixotropy, which substantially improves the gel strength and solves the problems of low yield point, rock carrying and poor borehole cleaning ability.…”
Section: In Drilling Fluidsmentioning
confidence: 99%
“…The synergistic effect of covalent micro-crosslinking enabled the DF to have excellent rheological and filtration properties even at 200 • C, which greatly improved the operational stability of the DF. Huang et al [17] synthesized a polyamide wax (TQ-1), which formed a weakly crosslinked gel structure in OBDF by hydrogen-bonded crosslinked. It was shown that TQ-1 could increase the ES values of OBDF, greatly improve the yield point and gel strength, and greatly reduce the sedimentation factor (SF).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional covalently bonded high molecular gels, supramolecular gels are mainly self-assembled by non-covalent bond interactions, which have reversible structure and high performance [29]. At present, the problem of good leakage has become particularly prominent, especially the problem of malignant leakage in complex drilling engineering [30,31]. The conventional hydrogel used for plugging has achieved good results in dealing with small and medium fractures and leakage of permeable drilling fluid.…”
Section: Introductionmentioning
confidence: 99%